Implementation of Minimum Demand Method (MDM) in Decide an Initial Feasible Solution of Transportation Problem - Nurmaulidar, Nurmaulidar; Yuni, Syarifah Meurah; Fauzan, Muhammad Atta (Syiah Kuala University, 2025)
This study investigates the effectiveness of the Minimum Demand Method (MDM) in determining an initial feasible solution (IBFS) for the Rastra rice distribution problem managed by Perum Bulog in West Sumatra, Indonesia. Unlike traditional methodsNorth-West Corner (NWC), Least Cost (LC), and Vogels Approximation Method (VAM)MDM prioritizes allocation to destinations with the smallest demand, aiming to minimize cost fragmentation and improve solution quality. The original transportation model was unbalanced, requiring a dummy source to achieve feasibility. IBFS values were computed using POM-QM for Windows 4, followed by optimality verification via the Modified Distribution (MODI) method. Results show MDM yields the lowest total cost at IDR 25,227,010, outperforming NWC (IDR 27,967,340), LC (IDR 25,821,810), and VAM (IDR 25,821,810). MODI confirmed MDMs solution as optimal, with zero improvement indices, validating its efficiency. Compared to the next-best method, MDM achieves a 2.3% cost reduction, and a 9.8% saving relative to NWC. This confirms MDMs superiority in generating high-quality IBFS without increasing computational complexity. The study demonstrates that MDM is not only simple and intuitive but also highly effective for large-scale public logistics systems, offering a practical alternative to conventional techniques in real-world distribution planning.